ISLAMIC EDUCATION TEACHES EMOTIONALLY INTELLIGENT STUDENTS IN DIGITAL ERA - Muksalmina (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
Islamic education represents a pivotal response to globalization, shaping the ethical and moral fabric of society to cultivate devout and virtuous individuals (Piety, 2020). This study aims to explore the role of emotional intelligence in Islamic education, particularly in the context of digitalization and its developmental pathways. Employing a qualitative research approach, this study relies on literature review as its primary data source, offering a descriptive analysis to illuminate key insights. The findings underscore the necessity for Islamic education to innovate its pedagogical strategies, fostering active student engagement through strategic planning aimed at enhancing emotional intelligence. This contributes both scientifically and strategically to the advancement of Islamic education, emphasizing the development of students' self-emotional intelligence.